Impact of HIV on tuberculosis in the developing world and how to manage it - Harries, Anthony D. (Henry Stewart Talks, 2013)
Global HIV-Tuberculosis, Historical context, Interaction between the two pathogens (HIV and Mycobacterium tuberculosis), The Framework for Tuberculosis Control "DOTS", The effect of HIV on Tuberculosis control with respect to programme delivery and patient management, The health sector response, The WHO Interim Policy on decreasing the joint burden of HIV and tuberculosis, Mechanisms for collaboration, Preventing TB in HIV-infected persons, Treating HIV in patients with TB, Conclusion